PENGEMBANGAN E-MAGAZINE BERBASIS PROYEK UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PADA MATERI KLASIFIKASI MAKHLUK HIDUP - Rindyana Kusuma; Ratno, Puspoko Ponco; Maiyanti, Aziza Anggi; Pradana, Mochamad Desta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a project-based e-magazine as a learning medium on the topic of classification of living organisms to improve students’ science process skills. The research employed a Research and Development (R&D) approach using the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The trial subjects were 29 seventh-grade students at MTsN 3 Kediri. The research instruments included validation sheets, science process skills questionnaires, and pretest-posttest items. Data analysis techniques involved validity and reliability tests, normality tests, paired sample t-tests, and N-Gain calculations. The validation results indicated that the e-magazine was highly valid, with an average expert score exceeding 80%. The reliability test showed a Cronbach’s Alpha of 0.932 (highly reliable). The paired sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest scores. The average N-Gain score was 0.544, categorized as moderate. Therefore, the project-based e-magazine is considered feasible and moderately effective in improving students’ science process skills, particularly in observing, classifying, concluding, and communicating.